Prevalence of behavioral and mental disorders in Manizales, Colombia - Daniel Alfredo Landinez; Anyerson Gomez Tabares; Daniel Rincon Cuartas (Mediterranean Journal of Clinical Psychology, 2021)
Background: Mental and behavioral disorders are responsible for the largest proportion of the global burden of disease; yet, there is sound evidence that the prevalence of these disorders is variable worldwide. Indeed, such disorders are highly inconsistent in Manizales, Colombia when compared to national data.